JAKOŚĆ W MEDYCYNIEThe chi-square independence test and its application in the clinical researches - Kwasiborski, Przemysław J.; Sobol, Maria (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
The chi-square test is one of most commonly used statistical tests in medical science. This test is used to verify the null hypothesis (H 0 ) which assumes that there is no significant difference between expected and observed data. The null hypothesis is rejected if chi-square value p is less than 5%. A comprehensive review of a chi-square test application and its limitations are presented.